PERSEPSI MASYARAKAT TERHADAP APARAT PENEGAK HUKUM DAN LEMBAGA PENGADILAN DI INDONESIA - Farid Th Musa (Universitas Negeri Gorontalo, 2010)
the atmosphere of the anniversary of indepedence august 17, 2010 is an opportune moment to reflect on the ways the law during this run which is full of criticism and cynisism from the public view.in this paper,the author wants to changes the ways in primitiv state.laws must be placed into a more intelligent way of meaning ful and cultured according to the view that developed in this paper namely the sociology of law. law enforcement agen cies and courts have a greater burden of responcibility in implementing the law in the midst of the community.for that quality performance of law enforcement agencies and courts must be improved.negative views of society must be changed quikly to grow back better publik trust.not easy to changed things,we need morality and professionalism of law enforcement agencies and courds. Keywords: public perception,Law Enforcement Agencies,Court,sociologi of Law.